CORPORATE GOVERNANCE, INTELLECTUAL CAPITAL, FINANCIAL PERFORMANCE DAN FIRM VALUE PADA PERUSAHAAN FARMASI DI BEI - Luluk Musfiroh; Dhani Ichsanuddin; Dwi Suhartini (Jurnal MEBIS (Manajemen dan Bisnis), 2018)
This study aims to examine the effect of corporate governance, intellectual capital on firmvalue with financial performance as an intervening variable inPharmaceutical companies in Indonesia Stock Exchangein period 2011-2015. The sample was chosen using purposive sampling method and obtained 35 financial statements and company annual report to be sampled. Data analysis used is path analysis withSPSS 23.The results of this study indicate thatmanagerial ownership, institutional ownership and intellectual capital have a negative effect tofirm value. Independent commissioners and audit committees have no effect to the firm value.Financial performance is not an intervening variable between managerial ownership, institutional ownership, independent commissioner and audit committee tofirm value, but financial performance is an intervening variable between intellectual capitaltofirm value. Financial performance has an effect tofirm value.